Manajemen Terapi Dzikir pada Pasien Hipertensi (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The purpose of this study was to investigate how dhikr therapy can lessen psychopathological symptoms. Eighteen hypertension patients in all were chosen as volunteers and divided into two groups: experimental and control. While the control group (n = 9) was placed on a waiting list, the experimental group (n = 9) received the therapy. The Brief Symptoms Inventory (BSI), which measures psychopathological symptoms before therapy (pretest), after therapy (posttest), and during a two-week follow-up test, was administered to all participants. With Z = -3.339 and p = 0.000, data analysis using the Mann-Whitney U revealed a significant decrease in symptoms. The findings confirmed the theory that psychopathological symptoms were alleviated by dhikr treatment. This study concluded that spiritual therapy plays a significant influence in lowering psychological symptoms.